Jurnal Hubungan Faktor Maternal Terhadap Kejadian Preeklampsia Pada Kehamilan - Dian Pratiwi (Jurnal Medika Hutama, 2020)
Background: Maternal Mortality Rate (MMR) is an indicator of health and mortality of pregnant women where high MMR can indicate low economic conditions and health services in antenatal and obstetrics. AKI can be caused due to causes that occur directly or indirectly, the direct cause is usually due to birth or childbirth, while the indirect cause is due to a disease experienced during pregnancy or a history of disease. One of the indirect causes is preeclampsia which occurs during pregnancy and there are maternal factors that influence the occurrence of these complications. The content in this study uses the rivew literature method from 18 international journals and Indonesian journals through the media PubMed, NCBI, and Google Scolar. Several journals mention maternal factors that influence the occurrence of complications of preeclampsia, namely age, BMI, primigravida, and nutrition in the form of vitamins. In several journals it was found that age that affected was <20 and> 35 years old, and several journals also stated that the Body Mass Index (BMI) ≥ 25 kg / m2, primigravida factors can have an effect because pre-delivery stressors will increase blood pressure and if a deficiency of vitamin B12 and folic acid can be associated with a high level of hemosity in the body which can lead to preeclampsia. In conclusion, it can be seen that there are several maternal factors that most influence preeclampsia, namely age and BMI.